2010
DOI: 10.3390/s100908275
|View full text |Cite
|
Sign up to set email alerts
|

Study of a QCM Dimethyl Methylphosphonate Sensor Based on a ZnO-Modified Nanowire-Structured Manganese Dioxide Film

Abstract: Sensitive, selective and fast detection of chemical warfare agents is necessary for anti-terrorism purposes. In our search for functional materials sensitive to dimethyl methylphosphonate (DMMP), a simulant of sarin and other toxic organophosphorus compounds, we found that zinc oxide (ZnO) modification potentially enhances the absorption of DMMP on a manganese dioxide (MnO2) surface. The adsorption behavior of DMMP was evaluated through the detection of tiny organophosphonate compounds with quartz crystal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…QCMs have been proven to be reliable in the field of electrochemistry (Paulo Tde et al, 2013; Sun et al, 2013a, 2013b), in petroleum characterization (Pejcic et al, 2011; Ueyama et al, 2002), in environmental chemistry (Nicolini et al, 2012), material science (Pei et al, 2010) and more interestingly in the development of biosensors (Bouchet-Spinelli et al, 2013; Eom et al, 2013; Guntupalli et al, 2013; Wangchareansak et al, 2013) which are valuable for disease diagnosis. QCMs also found a great interest in the monitoring of the affinity constants defining a given substrate-ligand interaction (Lebed et al, 2006; Li et al, 2013; Mori et al, 2009; Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…QCMs have been proven to be reliable in the field of electrochemistry (Paulo Tde et al, 2013; Sun et al, 2013a, 2013b), in petroleum characterization (Pejcic et al, 2011; Ueyama et al, 2002), in environmental chemistry (Nicolini et al, 2012), material science (Pei et al, 2010) and more interestingly in the development of biosensors (Bouchet-Spinelli et al, 2013; Eom et al, 2013; Guntupalli et al, 2013; Wangchareansak et al, 2013) which are valuable for disease diagnosis. QCMs also found a great interest in the monitoring of the affinity constants defining a given substrate-ligand interaction (Lebed et al, 2006; Li et al, 2013; Mori et al, 2009; Tan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[45] Also, attenuated total reflectance (ATR) IR spectroscopy has been applied to as tudy of the interactions of DMMP with amorphous a-SiO 2 grown by plasma oxidation of Si, on Al 2 O 3 , and on AlOÀ(OH) surfaces as af unction of the relative humidity. [47] Acidic polymers for surface acoustic wave sensorsa nd inverse gas chromatography of DMMP were recently developed. [47] Acidic polymers for surface acoustic wave sensorsa nd inverse gas chromatography of DMMP were recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…[46] Additionally,acompositen anostructured film comprised of MnO 2 nanofibers modified with ZnO was prepared on aq uartzc rystal microbalance for nerve-gas sensing. [47] Acidic polymers for surface acoustic wave sensorsa nd inverse gas chromatography of DMMP were recently developed. [48,49] The supramolecular approach, even if it is lessu sed, [50] gives alternative pathways to detect this class of CWAs.…”
Section: Introductionmentioning
confidence: 99%
“…11.2d). Pei et al [52] utilized ZnO-modified MnO 2 nanofiber-coated QCM sensor to detect the tiny dimethyl methylphosphonate which is a significant environmental and food chain pollutant. The experimental data revealed that the sensor could detect 35 ppb of DMMP in 300 s and possessed good selectivity and reversibility.…”
Section: Quartz Crystal Microbalance (Qcm) Sensormentioning
confidence: 99%